Microwave Assisted Synthesis, Spectral Studies and Antibacterial Activity of 1,5-benzodiazepines Derivatives on a Solid Surface - Devpura, Anju; P. Singh, Jayant; Jaitawat, Neetu; Rathore, Renu; Kumawat, Monika; S. Dulawat, Shiv (Asian Journal of Chemistry, 2012)
Chalcones are well known intermediates for synthesizing various heterocyclic compounds. They have been utilized for the synthesis of various substituted benzodiazepines by the reaction of o-phenylenediamine. In present investigation we have carried out the reaction under both conventional method and microwave assisted organic synthesis technique in presence of basic alumina. The procedure lead to improved efficiency of basic alumina, better conversion within shorter period, clean, efficient, safe methodology with higher selectivity, yield and purity of compounds in comparision to conventional methods. The structures of compounds are supported by spectral and analytical data. The structure-activity relationships of synthesized compounds have also been studied.